A comprehensive analysis on Symplocos racemosa Roxb.: Traditional uses, botany, phytochemistry and pharmacological activities. (2nd April 2016) - Acharya, Niyati; Acharya, Sanjeev; Shah, Unnati; Shah, Ripal; Hingorani, Lal
Abstract: Ethnopharmacological relevance: Symplocos racemosa Roxb. belongs to a unigeneric family Symplocaceae, known as lodhra in Sanskrit; is a small evergreen tree, found throughout the tropical and sub-tropical countries. Ethnobotanical literature indicates use of S. racemosa in treatment of eye disease, skin diseases, ear diseases, liver and bowel complaints, tumors, uterine disorders, spongy and bleeding gums, asthma, fever, snake-bite, gonorrhea and arthritis. The main aim of this review is to provide detailed phytopharmacological profile on S. racemosa in support with the traditional practices and ethnomedicinal uses. Materials and methods: All relevant worldwide accepted databases have been searched for the name " S. racemosa " along with other literature from Indian Classical texts and Pharmacopoeias. The accessible literatures available on S. racemosa, were collected through electronic search on Pub med, Scopus, Science direct and traditional reports. Results: S. racemosa is important Indian traditional drug used in many Ayurvedic and herbal formulations for treatment of liver as well as uterine disorders and leucorrhea. Majority of phytopharmacological reports are on stem bark of the plant which include anti-cancer, hepatoprotective, anti-oxidant, anti-androgenic effect, anti-inflammatory, wound healing activity and anti-diabetic effects. Phytochemical studies indicated presence of many phenolic glycosides like symplocoside, triterpenoids like betulinic acid, acetyloleanolic acid and oleanolic acid and flavonoids like quercetin which might have contributed to the observed protective effects. Conclusion: Many ethnobotanical claims have been confirmed through systematic in-vitro and in-vivo pharmacological studies on different extracts of stem bark and isolated constituents. However, systematic studies on the bio-markers are desirable to establish mode of action and to validate the traditional claim in clinical practice after proper safety assessment. The conservation data of genus Symplocos showed risk of extinction due to restricted distribution in the wild hence systematic techniques should be developed for the maintenance of this plant. Graphical abstract: